Mandarahi Kapalo Banda :Pemahaman Masyarakat Simancuang terhadap Ruang Hidup dan Penyelamatan Hutan - Riche Rahma Dewita (Universitas Andalas, 2022)
Mandarahi Kapalo Banda is a traditional and local wisdom of Simancuang communities. The ceremony is usually performed after the rice harvest season where the communities come together to mandabiah kabau nan gadang (slaughtering buffalo), cook the buffalo meat, pray, and eat. This tradition came after a crop failure occured in 1980 due to hogs pests. At that time, the only way to cope with these wild pigs issues was to plant the rice together and in unison. Mandarahi Kapalo Banda is not only a local tradition to feel grateful towards the harvest but also as an attempt to ensure the success of future harvest. This tradition is a valuable momentum to agree the schedule of rice planting to save the communities' harvest. As the result, the Simancuang communities need a stable irrigation for their 180 ha rice fields covering from the upstream area to the downstream area of Simancuang Region. Therefore, the communities build an agreement and regulations to protect their upstream areas in the surrounding forests, set the spatial area management for their settlement, set the spatial area for rice field, and other regulations regarding the natural resource utilization around them. This description will reveal how the Simancuang communities understand their environment condition, enable them to define their environment to regulate their neighborhood which will eventually impact the forest sustainability.